ChemInform Abstract: High‐Pressure Synthesis and Characterization of Incompressible Titanium Pernitride. Issue 23 (May 2016) - Bhadram, Venkata S.; Kim, Duck Young; Strobel, Timothy A.
Abstract: TiN2 is prepared in a laser‐heated diamond anvil cell using pre‐compressed TiN flakes surrounded by a dense N2 pressure transmitting medium (Re gaskets, 73 GPa, 2400 K).